The post-2025 ASEAN agrifood landscape: what next? - Teng, Paul (2024)
The ASEAN agrifood landscape – food produced from agriculture – has changed much since two key guiding documents were conceived – The ASEAN Vision and Strategic Plan of Action for Food, Agriculture and Forestry, 2016-2025, and the ASEAN Economic Community Blueprint, 2025. New players and new influencing factors are now at the forefront, and more than ever, ASEAN has to balance economic growth-related food security and safeguarding the environment while considering sustainable food systems that provide livelihoods for smallholder farmers and affordable, safe food for consumers.